A voyage across limestone landscapes into the subterranean realm of caves - Peter Gedei (Acta Carsologica, 2020)
Only few  cave photography books chave reached a wide international recognition.  The best example is the book on Lechugilla Cave, published by  Speleo Projects in 1991. The book has been an inspiration to many cave photographers. Incredible photos from the »most beautifull cave in the world« were shot by two teams, led by  Urs Widmer Kevin Downey and Sure Ballman. The book also inspired Max Wisshak, one of the most recognised cave photographers, who dedicated his second book to the late photographer and publisher Urs Widmer.